Application of Spinel and Hexagonal Ferrites in Heterogeneous Photocatalysis - Zuzanna Bielan (MDPI AG, 2021)
Semiconducting materials display unique features that enable their use in a variety of applications, including self-cleaning surfaces, water purification systems, hydrogen generation, solar energy conversion, etc. However, one of the major issues is separation of the used materials from the process suspension. Therefore, chemical compounds with magnetic properties have been proposed as crucial components of photocatalytic composites, facilitating separation and recovery of photocatalysts under magnetic field conditions. This review paper presents the current state of knowledge on the application of spinel and hexagonal ferrites in heterogeneous photocatalysis. The first part focuses on the characterization of magnetic (nano)particles. The next section presents the literature findings on the single-phase magnetic photocatalyst. Finally, the current state of scientific knowledge on the wide variety of magnetic-photocatalytic composites is presented. A key aim of this review is to indicate that spinel and hexagonal ferrites are considered as an important element of heterogeneous photocatalytic systems and are responsible for the effective recycling of the photocatalytic materials.